2013
DOI: 10.1515/hsz-2012-0326
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynonenal-stimulated activity of the uncoupling protein in Acanthamoeba castellanii mitochondria under phosphorylating conditions

Abstract: The influence of 4-hydroxy-2-nonenal (HNE), a lipid peroxidation end product, on the activity of the amoeba Acanthamoeba castellanii uncoupling protein (AcUCP) in isolated phosphorylating mitochondria was studied. Under phosphorylating conditions, exogenously added HNE induced GTP-sensitive AcUCP-mediated mitochondrial uncoupling. The HNE-induced proton leak decreased the yield of oxidative phosphorylation in an HNE concentration-dependent manner. The present study describes how the contributions of ATP syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…This G(m) increase is concentration-dependent and exhibits a typical saturation kinetics. In addition, for the amoeba Acanthamoeba castellani it was shown that the HNE induced UCP-mediated mitochondrial uncoupling is GTP-sensitive [ 228 ].…”
Section: Biochemical Targets Of Hnementioning
confidence: 99%
“…This G(m) increase is concentration-dependent and exhibits a typical saturation kinetics. In addition, for the amoeba Acanthamoeba castellani it was shown that the HNE induced UCP-mediated mitochondrial uncoupling is GTP-sensitive [ 228 ].…”
Section: Biochemical Targets Of Hnementioning
confidence: 99%
“…Therefore, the unloading of the H + gradient with the help of uninhibited AAC/UCP might provide the time needed to regenerate active AAC for ADP/ATP antiport via compensatory expression. Hydroxynonenal-stimulated uncoupling in mitochondria may occur under phosphorylating conditions (Woyda-Ploszczyca and Jarmuszkiewicz 2013 ), supporting the hypothesis that organelles fight to survive in response to a CATR-induced increase in the HNE level. The efficacy of this type of first-line antioxidant defense, i.e., prevention of respiratory chain overreduction and downstream detrimental effects, such as excessive ROS generation/lipid peroxidation, depends on the relative concentrations of effectors alleviating, e.g., CATR, and factors driving, e.g., HNE, H + translocation through AAC and UCP across IMM.…”
Section: Target Proteins Of Atractyloside and Carboxyatractyloside Ot...mentioning
confidence: 65%
“… 2003 ; Parker et al. 2008 ; Woyda-Ploszczyca and Jarmuszkiewicz 2011 , 2012 , 2013 , 2014a , 2014b , 2017 ). Regarding the effectiveness of GDP and GTP in hindering UCP, GTP is a relatively stronger, more specific, and more ‘diagnostic' (physiological) blocker than GDP in different organisms (Woyda-Ploszczyca and Jarmuszkiewicz 2011 , 2014a , 2017 ).…”
Section: Laboratory Detection and Use Of Atractyloside And Carboxyatr...mentioning
confidence: 99%
See 1 more Smart Citation
“…A. castellanii has been more thoroughly studied experimentally than most other free living amoebae. It has been used as a model organism for studies on the cytoskeleton, cell movement, gene regulation and mitochondrial bioenergetics [9] , [10] , [11] . The role of STATs previously found in slime molds has been assigned mostly to the development of multicellular structures that are facultatively formed by D. discoideum cells [12] .…”
Section: Introductionmentioning
confidence: 99%